Phenotypes and distribution of mucosal memory B-cell populations in the SIV/SHIV Rhesus macaque model - Demberg, Thorsten (2014)
As vaccine-elicited antibodies have now been associated with HIV protective efficacy, a thorough understanding of mucosal and systemic B-cell development and maturation is needed. We phenotyped mucosal memory B-cells, investigated isotype expression and homing patterns, and defined plasmablasts and plasma cells at three mucosal sites (duodenum, jejunum and rectum) in rhesus macaques, the commonly used animal model for pre-clinical vaccine studies. Unlike humans, macaque mucosal memory B-cells lacked CD27 expression; only two sub-populations were present: naïve (CD21(+)CD27(−)) and tissue-like (CD21(−)CD27(−)) memory. Similar to humans, IgA was the dominant isotype expressed. The homing markers CXCR4, CCR6, CCR9 and α4β7 were differentially expressed between naïve and tissue-like memory B-cells. Mucosal plasmablasts were identified as CD19(+)CD20(+/−)HLA-DR(+)Ki-67(+)IRF4(+)CD138(+/−) and mucosal plasma cells as CD19(+)CD20(−)HLA-DR(−)Ki-67(−)IRF4(+)CD138(+). Both populations were CD39(+/−)CD27(−). Plasma cell phenotype was confirmed by spontaneous IgA secretion by ELISpot of positively-selected cells and J-chain expression by real-time PCR. Duodenal, jejunal and rectal samples were similar in B-cell memory phenotype, isotype expression, homing receptors and plasmablast/plasma cell distribution among the three tissues. Thus rectal biopsies adequately monitor B-cell dynamics in the gut mucosa, and provide a critical view of mucosal B-cell events associated with development of vaccine-elicited protective immune responses and SIV/SHIV pathogenesis and disease control.